KNOWLEDGE, PERCEPTION AND PRACTICE OF RADIATION PROTECTION IN PAEDIATRIC IMAGING AMONGST IIUM MEDICAL IMAGING STUDENTS - SALLEH, NUR SYAFIQAH; CHE MOHAMED, NORFARIHA; MOEY , SOO-FOON (International Journal of Allied Health Sciences, 2021)
Introduction: The effects of ionizing radiation are more prevalent in children than in adults because the cells in children are still growing and they have a longer life span compared to the adults. As such, safety measures must be undertaken to minimize the medical radiation effects. Objective/aims: This study is to determine the knowledge, perceptions and practices of IIUM Medical Imaging students on paediatric radiation protection and its’ importance in paediatric imaging. Materials and methods: This cross-sectional study was carried out on 63 randomly selected second to fourth year undergraduate Medical Imaging students at the International Islamic University Malaysia (IIUM), Kuantan from Jun 2019 to July 2020. Data was collected using a self-developed questionnaire. The relationship between knowledge and perceptions as well as perceptions with practices on paediatric radiation protection and its’ importance in imaging were obtained using Spearman rho correlation test. Results: Most respondents have high level of knowledge, perceptions and practices on paediatric radiation protection and its’ importance in paediatric imaging. However, no significant relationships were found between knowledge of paediatric radiation protection and perceptions on the importance of paediatric radiation protection as well as the perceptions on the importance of paediatric radiation protection and practices of radiation protection. Conclusion: The practice of radiation protection in paediatric imaging is not only influenced by knowledge, perceptions and practices but also other contributing factors such as personal value and experiences.